Activity Assay of Glutathione S-Transferase (GSTs) Enzyme as a Diagnostic Biomarker for Liver Hydatid Cyst in Vitro. - Lila Moatamedi Pour; Ali Farahnak; Mohamadbagher Molaei Rad; Taghi Golmohamadi; Mohamadreza Eshraghian (Tehran University of Medical Sciences, 2014)
The aim of this study was to detect the Glutathione S-Transferase(GST) enzyme activity of healthy / cystic liver as a diagnostic biomarker for hydatidosis. In order to compare with liver tissue, the level of the GSTs enzyme activity of parasite was also determined.Parasites were collected from sheep liver tissue with hydatid cysts at a local abattoir and washed with PBS buffer. Collected parasites and liver tissues were sonicated or homogenized respectively. Extract solution samples were centrifuged and stored at - 20°C. GST enzyme activities were measured in the extract of parasite and liver tissue samples (healthy and infected livers). Protein amounts and protein bands were detected using Bradford and sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) methods respectively. To determine significant difference between two groups, two-sample t-test was performed.GST specific activities of healthy / infected livers and parasites were estimated 304, 1297 and 146 U/ml/mg respectively. Significant higher GST specific activities in cystic liver than healthy liver was observed (P